A study on students’ satisfaction and return intention to Dataran Cendekia food kiosk in Universiti Teknologi Mara (UiTM) Shah Alam / Amizar Mohd Amin - Mohd Amin, Amizar (2013)
Customer satisfaction is one of the most essential factors in ensuring the long-term financial success of any organization. Previous marketing research suggested that customer satisfaction was influenced by the quality of the organization's core offerings. Customer satisfaction is a situation where customer expectations on the service and delivery met their needs and wants. To meet the needs and wants of the customer, various aspects should need to be consider and it might influenced by their age group, education background, income and their social life. Previous experience also influenced the customer satisfaction which demands the organizations to examine trends of their customer behavior and the delivery process provided. Understanding student’s demands and level of expectations was the vital parts for the university in evaluate their foodservices. It will be the determinants of students’ satisfaction whereby will effected their selection. This study empirically investigates the most influential factor related to customer satisfaction and return attention. This study finding clearly reveals that the most influential factor related to customer satisfaction and return attention was the service provided at the food kiosk in Dataran Cendekia. Service is positively accepted by the students’ who occupied the food kiosk. In addition the services practiced by the food kiosk operators have also implicated the students return intention due to the impression given. It is wise to say that ongoing effort conducted by the university authorities have a positive impact on the kiosk operator’s service delivery. These positive indications have provided significant implications for the university authorities especially the Division of Student Affairs, Dataran Cendekias’ food kiosks operator and future study on customer satisfactions.